Preparation and analysis of the thermal properties of non-toxic eco-friendly vegetable based oils. Issue 1 (October 2020) - Sathishkumar, S D; Rajmohan, T
Abstract: Cutting fluids play an important role in increasing the efficiency of the production system. Vegetable based cutting fluids produce less harmful effects to the environment thereby leading to the cleaner production system. In the present study, vegetable oils such as Neem and Karanja oils are blended in three different proportions which are used to improve the thermal performance of the vegetable based cutting fluids. Density, viscosity, flash point and fire point are the quality parameters used to analyze the thermal properties of vegetable oils were also studied. Triple Necked Round Bottom flask setup is used for mixing the two vegetable oils in different proportions. The experimental results reveal that the combination of 25% Neem and 75% Karanja proves to be the efficient vegetable oil for sustainable production in the modern industries.